2015
DOI: 10.1186/s13633-015-0015-1
|View full text |Cite
|
Sign up to set email alerts
|

Noonan syndrome and Turner syndrome patients respond similarly to 4 years’ growth-hormone therapy: longitudinal analysis of growth-hormone-naïve patients enrolled in the NordiNet® International Outcome Study and the ANSWER Program

Abstract: BackgroundTurner syndrome (TS) and Noonan syndrome (NS) are distinct syndromes associated with short stature and other similar phenotypic features. We compared the responses to growth hormone (GH) therapy of TS and NS patients enrolled in the NordiNet® International Outcome Study (IOS) or the American Norditropin Studies: Web-Enabled Research (ANSWER) Program, which collect information on GH therapy in clinical practice.MethodsRepeated-measures regression analysis was performed on change in height standard dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 37 publications
2
25
0
Order By: Relevance
“…A subsequent publication from the multinational KIGS data reported that 89% of GH-treated patients with isolated GHD reached a NAH within their genetic potential with most of the height gain occurring during the prepubertal years (5). Finally, a recent publication on data from the ANSWER Program, a significant negative association between age at GH treatment start and NAH SDS was observed in a cohort of older children with isolated GHD and delayed skeletal maturation (6). …”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…A subsequent publication from the multinational KIGS data reported that 89% of GH-treated patients with isolated GHD reached a NAH within their genetic potential with most of the height gain occurring during the prepubertal years (5). Finally, a recent publication on data from the ANSWER Program, a significant negative association between age at GH treatment start and NAH SDS was observed in a cohort of older children with isolated GHD and delayed skeletal maturation (6). …”
Section: Discussionmentioning
confidence: 93%
“…We therefore consider the present analysis to add weight and further expand on the evidence reported in the existing literature (4, 5, 6, 8, 13). …”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…The age gap of the girls at the time of growth hormone implementation was significant and ranged from 3 to 14 years. The results of previous studies in other centers indicate a lack of significant influence of the initiation age and duration of rhGH therapy [12][13][14], while others imply an important role of these factors [11]. However, Ping-Yi Hsu et al stress that early initiation of growth hormone therapy allows the induction of maturation at the right time [15].…”
Section: Discussionmentioning
confidence: 98%